Dermatopathology of Caprine Scabies and Protective Immunity in Sensitised Goats Against Sarcoptes scabiei Reinfestation - Tarigan, Simson (Indonesian Animal Sciences Society, 2002)
The purpose of this study was to compare macroscopic dermatopathology in naïve and sensitised goats, and to assess protective immunity possessed by sensitised goats against Sarcoptes scabiei challenge. Eighteen goats were allocated evenly into 3 groups; group 1 sensitised with the mite twice, group 2 once and group 3 was not sensitised (naïve). Sensitisation was done by infesting goats with the mites on the auricle and infestation was allowed to progress for 7 weeks, then the goats were treated with Ivermectin to obtain complete recovery. After sensitisation, all sensitised and naïve goats were infested with the mites on the auricles. Infestation in the sensitised goat caused severe immediate hypersensitivity that resulted in severe peracute pustular dermatitis. After one week, however, the lesion waned slowly. At 7 weeks post infestation, the remnant of lesion could only be perceived by palpation on the primary site of infestation as a mild papular dermatitis. Infestation on the naïve goats, in contrast, produced slowly progressing lesions which at 7-week post infestation, it ended up with severe crusted scabies affecting almost the whole skin. Antigens responsible for the immediate hypersensitivity which are supposedly contained in the mite secretions or excretions are immunologically protective but unlikely to have the capacity to induce a complete protection against mite challenge in immunised animals. This notion is based on the fact obtained from this study that goats sensitised twice did not possess a higher immune protection against mite challenge than goats sensitised once. Key words: Sarcoptes scabiei var. caprae, sensitisation, protective immunity, immediate hypersensitive